Hierarchies of belonging : national identity and political culture in Scotland and Quebec - Henderson, Ailsa (McGill-Queen's University Press, 2007)
"Henderson's Hierarchies of Belonging is a comparative exploration of two distinct cultures and the nationalistic leanings of their peoples. The book is a masterful aggregation of history, political culture, and issues of ethnicity and identity in both Scotland and Quebec."--Jacket.